Neonatal Abdominal Surgery, Our Experiences of 179 Cases (Faridpur Medical College Journal, 2019)
This is a retrospective study carried out in the Department of Pediatric Surgery, Faridpur Medical College Hospital and in Dr. Zahed Children Hospital at Faridpur, during the period of May 2002 to may 2016. Total 179 neonates were treated by laparotomy for intestinal obstruction after clinical diagnosis and resuscitation. The male to female ratio was 4:5. Most of the patients presented within 02 -25 days of age. In all cases diagnosis was done on history, clinical examination and investigations. The investigations were plain x-ray abdomen in all cases and contrast x-ray upper GIT in 10 cases and enema x-ray in 11 cases and sonogram in 15 cases. Serum electrolytes were not estimated in all patients. There were 34 postoperative mortality. We did loop diversion for 81 cases those who were in potential risk to develop septicemia. Oral feeding started at 3rd postoperative day in diversion cases and 4th postoperative day in resection and end to end anastomosis cases. Superficial wound infection was encountered in 39 cases. Anorectal malformation, IHPS, Exomphaious, Gastroschisis were not included in this study. Long term survival of neonatal abdominal surgery are excellent, however patients have substantial risk to develop intra-abdominal complications.Faridpur Med. Coll. J. Jul 2018;13(2): 82-84